2021
DOI: 10.1186/s43066-021-00104-9
|View full text |Cite
|
Sign up to set email alerts
|

Role of renal Duplex ultrasonography in evaluation of hepatorenal syndrome

Abstract: Background Hepatorenal syndrome is a potentially fatal complication of advanced liver disease. Markers for early diagnosis and identification of high-risk patients are lacking. Our aim was to evaluate the role of renal Duplex ultrasonography in the diagnosis and early prediction of hepatorenal syndrome. This study included 50 patients. Clinical assessment, liver function tests, hepatitis C virus antibody, kidney function tests, and abdominal and renal color Duplex ultrasound were done to all su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
1
1
0
1
Order By: Relevance
“…In our study RRI was in a positive correlation with serum creatinine (P < 0.05) and mean creatinine in patients with persistent AKI was significantly higher (P < 0.04). Similar to our results, Mohamad Sherif Mogawer et al (2021) (10) conducted a study on 50 patients suffering from child C liver cirrhosis and known normal baseline serum creatinine within one year before AKI. They showed that RI can predict hepato-renal syndrome (HRS) with 100% sensitivity and 67% specificity (cut off value > 0.77).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our study RRI was in a positive correlation with serum creatinine (P < 0.05) and mean creatinine in patients with persistent AKI was significantly higher (P < 0.04). Similar to our results, Mohamad Sherif Mogawer et al (2021) (10) conducted a study on 50 patients suffering from child C liver cirrhosis and known normal baseline serum creatinine within one year before AKI. They showed that RI can predict hepato-renal syndrome (HRS) with 100% sensitivity and 67% specificity (cut off value > 0.77).…”
Section: Discussionsupporting
confidence: 90%
“…RI is a sonographic index of intrarenal arteries and is measured as follows: (maximum systolic velocity−minimum-diastolic-velocity)/maximum systolic velocity. The normal range of RI is 0.50-0.70.For adults, RI value of 0.70 indicates normal renal vascular resistance (RVR), and all measures above 0.70 indicate increased RVR [10]. RRI was measured for all patients on admission and follow-up was done after 48 h, and the patients were followed till hospital discharge to detect correlation to outcome.…”
Section: Renal Arterial Duplex Measurementsmentioning
confidence: 99%
“…Это обусловлено высокой частотой развития дан ного осложнения, особенно у больных с тяжелым течением патологии печени. Так, по данным ис следований, от 25% до 50% пациентов с циррозом печени, поступающих на госпитальное лечение после эпизода декомпенсации, имеют признаки ГРС [10,11] УЗИ с допплеровским сканированием сосу дов является операторозависимым методом ис следования, однако при умелом использовании также с высокой эффективностью позволяет обна ружить признаки ГРС, особенно в развернутой ста дии [9,14].…”
Section: Discussionunclassified